Pengaruh Sikap Konsumen, Kepribadian, dan Budaya Terhadap Perilaku Konsumen Dalam Membeli Produk Deterjen Cair Konsentrat Merek Alfamart di Alfamart Cabang KH. Azhari 2 Palembang - Rian Andrianto; Destia Aktarina (P3M STIE Mulia Darma Pratama, 2020)
The formulation of the problem in this study is how the influence of consumer attitudes, personality, and culture partially on consumer behavior in buying concentrated liquid detergent products Alfamart brand at Alfamart, KH Branch. Azhari 2 Palembang? and how the simultaneous influence of consumer attitudes, personality, and culture on consumer behavior in buying liquid detergent concentrated product Alfamart brand at Alfamart, KH Branch. Azhari 2 Palembang ?. The samples taken in this study were 35 consumers who bought the alfamart concentrate liquid detergent product at Alfamart, KH Branch. Azhari 2 Palembang. The analysis method used is the verification method and multiple linear regression. Simultaneous test results obtained Fcount > Ftable (12.724 > 2.911) and sig. 0.000 <0.05, so the alternative hypothesis is accepted and the null hypothesis is rejected, it can be concluded that the variable consumer attitude (X1), personality (X2), and culture (X3) together have an effect on consumer behavior (Y) in buying concentrated liquid detergent products. Alfamart brand at Alfamart KH Branch. Azhari 2 Palembang. The result of the partial test (t test) can be explained: The variable consumer attitude (X1) has a significant effect on consumer behavior (Y), the value of tcount > ttable (2.101 > 1.696) and sig. 0,000 <0.05, so the consumer attitude variable (X1) has a significant effect on consumer behavior (Y) in buying liquid detergent product concentrate alfamart brand at Alfamart, KH Branch. Azhari 2 Palembang. Personality variable (X2) has a significant effect on consumer behavior (Y), the value of tcount > ttable (2.289> 1.696) and sig. 0.000 < 0.05, so the personality variable (X2) has a significant effect on consumer behavior (Y) in buying a liquid detergent product concentrate alfamart brand at Alfamart, KH Branch. Azhari 2 Palembang. Cultural variable (X3) has no significant effect on consumer behavior (Y), the value of tcount <ttable (0.833 < 1.696) and sig. 0.411 > 0.05, so the cultural variable (X3) does not have a significant effect on consumer behavior (Y) in buying liquid detergent product concentrate alfamart brand at Alfamart, KH Branch. Azhari 2 Palembang. The result of the coefficient of determination (R2) obtained is 0.508 explaining (50.8%) means that the variables of consumer attitudes (X1), personality (X2), and culture (X3) affect consumer behavior (Y) by 50.8% while the remaining 49,2% (100%-50.8%) is influenced by other variables not examined in this study.